A comparative study of stepping angiography and traditional segmental angiography in lower limb anterograde venography - Hongzhi Sun; Lei Qi; Guoliang Wang; Huagang Li; Peng Ji; Maoneng Hu (Journal of International Medical Research, 2025)
Objective To compare the application value of stepping angiography and traditional segmental angiography in lower limb anterograde venography. Methods A retrospective analysis was conducted among 95 patients who underwent lower limb anterograde venography at the Hefei Third People’s Hospital and the First Affiliated Hospital of Anhui University of Chinese Medicine from September 2021 to December 2024. Among them, 50 patients who underwent traditional segmental angiography were assigned to the control group, while 45 patients who underwent stepping angiography were assigned to the observation group. Comparative assessments were performed between the two groups regarding image quality, angiography time, absorbed radiation dose, contrast agent dosage, and incidence of complications. Results The image quality in the observation group was better than that in the control group. The average angiography time in the control group was 27.87 ± 4.98 min, while that in the observation group was 10.23 ± 2.88 min ( P  =   0.013). The average absorbed radiation dose in the control group was 4.65 ± 1.32 Gy, while that in the observation group was 3.53 ± 0.73 Gy ( P  =   0.008). The average contrast agent dosage in the control group was 69.42 ± 10.42 mL, while that in the observation group was 47.51 ± 8.14 mL ( P  =   0.011). Two complications occurred in the control group, while three occurred in the observation group ( P  =   0.339). Conclusion For lower limb venous lesions, stepping angiography is superior to traditional segmental angiography in terms of overall image quality and practicality. Stepping angiography is a simpler and quicker process, and only a small dose of radiation is absorbed by both doctors and patients; moreover, it requires a lower dosage of contrast agent. It plays an important objective guiding role in the decision-making of treatment plans for lower limb venous diseases.